Pertanggungjawaban Pidana Pelaku Abortus Akibat Pemerkosaan Menurut Hukum Pidana Dan Hukum Kesehatan - Sofyan Rauf (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
Comparison of Accountability in Murder Against the Law of Abortus Provocatus Due to Rape in Court Law and Health Law It is necessary to consider the legal instruments contained in Law Number 1 of 1946 concerning the Criminal Code, then the Provocatus Abortion Act is justified in the Criminal Code Submitting Article 48 of the Criminal Code concerning forced power. Article 75 of Law Number 36 of 2009 concerning Health provides normative space for the implementation of Abortus Provocatus due to reasons for medical change and rape with conditions set out in Article 76 of Law Number 36 Year 2009 which reads Before being responded to 6 (six) weeks.